An integrated transcriptome and microbial community analysis reveals potential mechanisms for increased immune responses when replacing silybum marianum meal with soybean meal in growing lambs - Zhang, Tianxi; Ren, Yanbo; Yang, Chao; Gebeyew, Kefyalew; Gao, Min; He, Zhixiong; Tan, Zhiliang (Frontiers in Microbiology, 2023)
Silybum marianum meal is a by-product that remains silymarin complex and is perceived as a potential-protein source. The potential and its mechanism of silybum marianum meal as a protein supplement in ruminants were evaluated by testing the growth performance, biochemical parameters, cytokine levels, gut transcriptome and microbial community profiles. Forty-two male Hulunbeier growing lambs (aged about 3-month-old; averaged body weight of 21.55 kg) were randomly divided into the CON (with 10% soybean meal) and SIL groups (with 10% silybum marianum meal). There was no significant difference in growth performance, feed intakes, or serum biochemical parameters between CON and SIL. The serum levels of IL-1β, TNF-α, TGF-β, HGF and VEGF were all increased (P < 0.05) in the SIL group as compared with the CON group. Transcriptome gene set enrichment analysis (GSEA) revealed that the core genes in the rumen from SIL group were enriched with fructose and mannose metabolism, while the core genes in the ileum were enriched for three biological process, including digestive tract development, positive regulation of MAPK cascade, and regulation of I-kappaB kinase/NF-kappaB signaling. The 16S rDNA results showed that the relative abundance of Bacteroidetes, Firmicutes, Synergistetes, and Verrucomicrobia in the rumen from SIL group was significantly higher than that in CON group (P<0.05), whereas Proteobacteria was significantly lower than that in CON group (P<0.05). In the ileum, there were no significant differences in the phylum-level classification of microbes observed. At the genus level, the relative abundances of Bifidobacterium and Ruminococcus in the ileum from SIL group were significantly higher than that in the CON group (P<0.05), whereas the relative abundance of Clostridium_XI was lower (P<0.05). Correlation analysis showed that Clostridium_XI was negatively correlated with VEGF, TGF-β, TNF-α and HGF (P<0.05). Core genes BMP4 and CD4 were negatively correlated with Clostridium_XI (P<0.05). Our results indicated that supplementing silybum marianum meal as a replacement for soybean meal resulted in increased cytokines production without affecting growth performance in growing lambs, and the enrichment of immune-related genes and altered microbial community in the ileum were contributed to the increased immune responses.